Exploring the impact of seashell powder and nano-silica on ultra-high-performance self-curing concrete: Insights into mechanical strength, durability, and high-temperature resilience - Sun Yitong; Alqurashi Muwaffaq; Mostafa Sahar A. (Reviews on Advanced Materials Science)
This study examines the impact of using seashell powder, shells mixed with nano-silica, and basic oxygen furnace slag as sand substitutes in addition to the internal curing regime. This study focuses on important factors related to material sustainability and the efficient use of resources. The comprehensive evaluation of mechanical properties, including compressive and tensile strength at different stages, provides a significant understanding of the performance improvements achieved with these innovative additives. Durability tests, which evaluate the absorption, water permeability, salt penetration, and sulfate resistance, advance our understanding of how these materials enhance the long-term durability of ultra-high-performance concrete (UHPC) under extreme environmental conditions. In addition, examining UHPC samples at high temperatures (350 and 700°C) and applying scanning electron microscopy. The improved mechanical strength and toughness achieved using seashells and nano-silica demonstrated the potential of these additives to create UHPC that is more sustainable and environmentally friendly. The results indicate that the addition of seashell powder slightly reduced the compressive strength. However, replacing cement with a blend of seashells and nano-silica led to an improvement ranging from 5 to 6% in compressive strength across various replacement ratios at 7, 28, and 90 days. The optimum strength is obtained at a 5% replacement ratio. Tensile strength also increased from 1.6 to 1.8 MPa when seashells were pre-mixed with nano-silica. The incorporation of nano-silica significantly enhanced the thermal stability of the seashells, resulting in a better residual strength of 84–93% at 350°C and ranged from 68 to 82% at 700°C. Furthermore, the combination of seashells and seashell powder with nano-silica notably improved durability by reducing the water permeability, sorptivity, and chloride penetration depth. The residual strength of UHPC showed greater improvement after exposure to a sulfate environment when the seashells were combined with nano-silica than when seashells alone were used and achieved 81 MPa compared to 69.1 MPa for the control mix and 74 MPa for seashells only. Overall, the inclusion of seashells pre-mixed with nano-silica in UHPC enhanced the microstructure at both normal and elevated temperatures.